Three new araphid diatoms (Bacillariophyta) from the Maritime Antarctic Region - van De Vijver, Bart; Morales, Eduardo A.; Kopalová, Kateřina (Phytotaxa, 2014)
A revision of taxa from the genus Staurosira and Staurosirella from the Maritime Antarctic Region, formerly identified as Staurosirella (Fragilaria) pinnata and Fragilaria alpestris, resulted in the description of three new taxa: Staurosira pottiezii Van de Vijver sp. nov., Staurosirella antarctica Van de Vijver & E.Morales sp. nov. and S. frigida Van de Vijver & E.Morales sp. nov. Detailed light (LM) and scanning electron microscope (SEM) observations are used to better characterize the morphology and ultrastructure of these three new taxa. Comparisons with similar taxa and the ecological preferences of each species are added. The revision of these species confirmed the endemic nature of the Antarctic diatom flora.